Hydrogen permeation in composite Pd-membranes prepared by conventional electroless plating and electroless pore-plating alternatives over ceramic and metallic supports. (9th November 2016) - Alique, D.; Imperatore, M.; Sanz, R.; Calles, J.A.; Giacinti Baschetti, M.
Abstract: Composite palladium membranes are attracting great attention for hydrogen separation and membrane reactor applications, due to the complete hydrogen selectivity with reasonably high permeability and suitable mechanical stability. These membranes are usually prepared by depositing a thin Pd layer over ceramic or metallic supports, which give to the system the necessary mechanical resistance. The Pd incorporation is generally made by electroless plating (ELP), although there is still no fully optimized and universally accepted method, and many researches are currently devoted to the generation of thin and homogeneous metallic coatings with good adhesion and resistance to real conditions. Among the many studies, very few compares directly the properties of the two different supports (metallic or ceramic) on the overall membrane structure and performance. In the present work, the permeation behavior of several Pd-composite membranes, prepared by conventional ELP and by a novel pore-plating method (ELP-PP) has been studied on both ceramic and metallic supports. The membrane prepared over a tubular ceramic support by conventional ELP shows a permeability in the range of 2.5–3.6·10 −6  mol s −1  bar −0.5  m, with nearly complete ideal selectivity and Pd thickness around 14 μm. With the alternative preparation method, ELP-PP, despite the lower Pd thickness, 8 μm, and also complete selectivity, lower hydrogen fluxes were observed with a permeability ranging from 5.8 to 8.5·10 −7  mol s −1  bar −0.5  m. This behavior can be explained by considering that the pore-plating method leads to a Pd deposition over the external surface of the support but also inside the pores, generating an effective Pd thickness higher than that obtained with the conventional ELP. In this manner, the real behavior of the membrane is equivalent to a conventional 33 μm thick palladium layer. Finally, these results are compared replacing the ceramic support by a metallic one (PSS), which led to an increase in the minimum thickness necessary to achieve a totally dense membrane (Pd thickness, 9 μm), and, consequently, to a reduction of the observed transmembrane flux. However, in this case a lower deposition of palladium inside the pores of the support is observed thus causing a lower resistance to the hydrogen permeation with respect to ceramic supported membranes. Highlights: Totally dense membranes over ceramic and metallic supports was achieved by ELP and ELP-PP. H2 permeability of 5.8·10 −7 –3.6·10 −6  mol s −1  bar −0.5  m and complete hydrogen selectivity. ELP-PP reduces the amount of Pd, but makes the H2 permeation difficult in ceramic supports. Additional resistance to H2 permeation is less accused for membranes prepared over PSS support.